Fate of the Earth - Andorfer, Gregory; Kiley, Richard; Walter, Chip; Bates, Robin; WQED (Television station : Pittsburgh, Pa.); National Academy of Sciences (U.S.); UNAPIX Entertainment ([New York]: UNAPIX Entertainment, 1995)
Explores the role of life in shaping the earth and its future
Series producer, Gregory Andorfer ; camera, Norris Brock ; editor, Clifford Hoelscher ; music, Jack Tillar, William Loose
Narrator, Richard Kiley
Keywords: Earth